Optimal Location of Distributed Generation and its Impacts on Voltage Stability - Manoj Kumar Nigam; V.K. Sethi (Institute of Advanced Engineering and Science, 2016)
Distributed generation (DG) technology is based on the renewable sources of energy. Now a day’s distributed generation plays an important role of power generation utilities to fulfill the increasing demand of power at the costumer’s site. A distributed generation is the small generation unit with capacity varying from kW (kilowatt) to few MW (megawatt). The main aim of this paper is to find the solution for optimal location of connecting DG and also the disturbances in the voltage fluctuations responds to imperfection of connecting DG. A test network of IEEE-30 bus system has been simulated using PSAT 2.1.7. The compensation methods have also been developed for filtering out the disturbances caused by the DG connection. The disturbance in the voltage profile is improved by minimizing the real and reactive power losses with the help of STATCOM. The proposed approach IEEE-30-bus system was tested and the result was discussed.